Methane Production and Bioactivity-A Link to Oxido-Reductive Stress - Boros, Mihály; Keppler, Frank (Frontiers in Physiology, 2019)
Biological methane formation is associated with anoxic environments and the activity of anaerobic prokaryotes (Archaea). However, recent studies have confirmed methane release from eukaryotes, including plants, fungi, and animals, even in the absence of microbes and in the presence of oxygen. Furthermore, it was found that aerobic methane emission in plants is stimulated by a variety of environmental stress factors, leading to reactive oxygen species (ROS) generation. Further research presented evidence that molecules with sulphur and nitrogen bonded methyl groups such as methionine or choline are carbon precursors of aerobic methane formation. Once generated, methane is widely considered to be physiologically inert, but several studies have found association between mammalian methanogenesis and gastrointestinal motility changes. In addition, a number of recent reports demonstrated anti-inflammatory potential for exogenous methane-based approaches in model anoxia-reoxygenation experiments. It has also been convincingly demonstrated that methane can influence the downstream effectors of transiently increased ROS levels, including mitochondria-related pro-apoptotic pathways during ischemia-reperfusion conditions. Besides, exogenous methane can modify the outcome of gasotransmitter-mediated events in plants, and it appears that similar mechanism might be active in mammals as well. This review summarizes the relevant literature on methane-producing processes in eukaryotes, and the available results that established its bioactivity. The current evidences suggest that methane liberation and biological effectiveness are both linked to cellular redox regulation. The data collectively imply that exogenous methane influences the regulatory mechanisms and signaling pathways involved in oxidative and nitrosative stress responses, which suggests a modulator role for methane in hypoxia-linked pathophysiologies.